Simulation based analysis of utilization, throughput and cycle time for surface coating industries - Ng, Victor Chong Lee. (2009)
Computer simulations and modeling have become a popular analysis technique to achieve the objectives of shortening cycle time and increasing resources' utilization and production throughput in manufacturing companies. Being able to model and analyze the dynamic characteristics of existing shopfloor activities, and being able to predict the behavior of shopfloor activities prior to the actual implementation of decisions will enable companies to plan and control their constrained resources. Furthermore, by evaluating the flow of raw materials and parts through workstations and examining the conflicting demands for limited resources, companies will be able to evaluate the physical layouts of shopfloor, equipment selection and operating procedures more effectively.